Dialogue, Reassurance and Understanding: Framing Political Translations during the 1980 and 1995 Quebec Sovereignty Referendums - McDonough Dolmaya, Julie (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
In Canada during the 1970s, 80s, and 90s, more than one thousand works – and about one hundred translations – were published on the topics of Quebec nationalism, independence movements, and sovereignty referendums, in both of Canada’s official languages. Despite the diversity of these publications, which included biographies, political analyses, and polemical essays, almost all the works touched on themes that have generated controversy in Canada. The paratexts in these translations are therefore an important resource that highlight perceived differences between the political opinions of Francophone and Anglophone readers. This article will analyze the paratexts in the English and French translations to show how the target language audience was encouraged to read a translation of a work that was very clearly not addressed to them, and which in some cases even criticized the very audience it now addressed. Finally, it will examine which features these English and French paratexts do and do not share, while trying to determine why these similarities and differences exist.